2018
DOI: 10.1021/acs.iecr.8b01055
|View full text |Cite
|
Sign up to set email alerts
|

Shortly Branched, Linear Dextrans as Efficient Binders for Silicon/Graphite Composite Electrodes in Li-Ion Batteries

Abstract: Dextran was evaluated as a binder material for graphite electrode, silicon electrode, and Si/graphite composite electrode in Li-ion cells. The performance was also compared with poly­(vinylidene fluoride) (PVDF) binder or lithium salt of poly­(acrylic acid) (LiPAA) binder. A graphite-rich Si/graphite composite electrode shows a reversible capacity of about 525 mAh g–1 at a C/5 rate and has an excellent cycling stability. An interface study using impedance spectroscopy, X-ray photoelectron spectroscopy, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Silicon has been recognized as one of the most promising negative electrode material for the lithium-ion batteries (LIBs) of next generation because of its high specific capacity (10 times that of graphite). The market share of silicon-based materials for LIBs has increased to 3–5% in the past three years because of the huge demand of electric vehicles. However, the large volume expansion of silicon (approximately 360%) during charge–discharge cycling leads to a rapid decline of the LIB capacity. To solve this problem, one of the effective methods is preparing silicon of nanostructures, such as nanoparticles, nanotubes, and nanowires. It is reported that the unique structure of silicon nanowires (SiNWs) can not only shorten radial Li-ion diffusion distance, but also enhance the structural robustness against volume variations, which makes SiNWs become a promising new negative electrode material for LIBs. SiNWs can be prepared by various methods, such as chemical vapor deposition, , laser ablation, , thermal evaporation, and template method . In spite of their respective specific merits, all of these methods have their own shortcomings, such as the high cost because of the requirements of energy-consuming equipments, high-purity Si substrates, and noble metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon has been recognized as one of the most promising negative electrode material for the lithium-ion batteries (LIBs) of next generation because of its high specific capacity (10 times that of graphite). The market share of silicon-based materials for LIBs has increased to 3–5% in the past three years because of the huge demand of electric vehicles. However, the large volume expansion of silicon (approximately 360%) during charge–discharge cycling leads to a rapid decline of the LIB capacity. To solve this problem, one of the effective methods is preparing silicon of nanostructures, such as nanoparticles, nanotubes, and nanowires. It is reported that the unique structure of silicon nanowires (SiNWs) can not only shorten radial Li-ion diffusion distance, but also enhance the structural robustness against volume variations, which makes SiNWs become a promising new negative electrode material for LIBs. SiNWs can be prepared by various methods, such as chemical vapor deposition, , laser ablation, , thermal evaporation, and template method . In spite of their respective specific merits, all of these methods have their own shortcomings, such as the high cost because of the requirements of energy-consuming equipments, high-purity Si substrates, and noble metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, these binders are not perfect for Si/graphite composite electrodes, and to the best of our knowledge, very few binders have been designed specifically for Si/graphite composite electrodes. During our search for the ideal binders, we have been intrigued by the finding that the graphite-rich Si/graphite composite electrode with PVDF binder loses its capacity very quickly during cycling, and after five cycles, the capacity is even lower than that of the graphite-only electrode . We essentially want to address the question “How could a small amount of silicon cause such a catastrophic effect on a composite that is very rich in graphite which is known for its good affinity to PVDF?”…”
Section: Introductionmentioning
confidence: 99%
“…随后, Jeong 等 [105] 利用天然黄原胶双螺旋超结构粘 化 学 学 报 综述 图 10 GG 与 LBG 粘结剂 Figure 10 GG and LBG binders (a) The chemical composition of guar gum (GG) and locust bean gum (LBG) [102] , (b) Schematic illustration of lithium-ion transfer in the GG binder [101] , (c) Electrochemical performance of SiNP anodes with different binders at 2100 mA•g -1 between 0.01 and 1.2 V [101] , (d) cycle performance with limited discharge capacity of 1000 mAh•g -1 at 1000 mA•g -1 [101] , (e) The symmetrical cycling performance of SiNPs with GG, LBG, Na-CMC and PVDF binders [102] 图 11 XG 粘结剂 [105] Figure 11 XG binder [105] (a) Chemical structure of XG binder, (b) Concept transfer from macroscopic to nanoscopic world and structural analogy of millipede to that of native-XG towards strong adhesion. A series of small legs in the millipede corresponds to multiple short side chains in native-XG (both colored in red 除以上粘结剂外, 研究人员还制备出新型耐高温粘 结剂结冷胶 [106] , 含有蛋白质以增加柔韧性的粘结剂卡 拉亚胶 [107] , 骨架构象能在锂化过程中转变的果胶 [108] , 从肠膜明串珠菌细菌中提取的天然多糖右旋糖酐 [109] , 模仿贻贝螺旋连接的儿茶酚共聚物 [110] 等粘结剂. [114,115] .…”
Section: 黄原胶粘结剂(Xg) 天然黄原胶粘结剂(Xg)是一种多糖粘结剂 基础 结构如图 11a 所示 具有与纤维素相同的骨架mentioning
confidence: 99%